The Why and How VR in Schools: A Preferred Future Pedagogic Mission by a Group of Worldwide Experts in VR and Education - Passig, David; Sharbat, Aviva (International Journal of Virtual Reality, 2001)
The exploration of virtual reality as a potential alternative space for human activity presents great challenges for contemporary thinking. This paper attempts to report a recent scholarly discussion about virtual reality and its implications for future K-12 education. This study did not aim to predict the future of VR in education. It aimed to evaluate the preferred mission of VR before the technology is widely used in schools. This study, in a sense, is taking a proactive approach in evaluating the needs and the appropriate educational theories to guide the development of VR before its widespread utilization. Other studies have aimed at observing evidence that show trends. However, this study with 50 worldwide VR experts assisted in drafting a preferred VR future pedagogic mission.